A preliminary assessment of the flora in Piagao Island, Nueva Valencia, Guimaras - Cerrada, Loufel Grace C.
The Philippines is recognized as one of the most biodiverse countries in the world when it comes to flora. This is due to its unique geographical setting that enables it to harbor great concentration of species wherein some are only endemic on its islands. Although there were many studies that explored different vegetation types in the Philippines, not enough data are available about small island flora except for its closely related vegetation type on limestone forests. This study determined the island flora on a small island of Piagao in Nueva Valencia Guimaras in terms of its community structure and distribution. Specifically, this study (1) described, identified, classified the flora and, (2) described the community structure in terms of species composition, stand height, stand basal area, importance value, and Shannon-Wiener Index of Diversity. Results showed a total of 61 species under 32 families were recorded. Family Fabaceae dominated the flora among other families represented. Cerbera manghas, Terminalia foetidissima, Salacia wenzelii, Dendrolobium umbellatum and Vitex parviflora were some of the dominant species with Cerbera manghas having the highest importance value at Iv=63.8. The stand basal area for Piagao island was 25.5 m2/ha and the Shannon-Wiener Index of Diversity as of the assessed plants was H?=1.23. Invasive species such as Acacia mangium, Bambusa blumeana., Dracaena reflexa, Lantana camara and Leucaena leucocephala were also present on the island. There were a greater number of seedlings (55%) than trees (31%) and saplings (14%) indicating its development into a more diverse island with proper handling, conservation and preservation.